Commercial inoculants in Baja California, Mexico: quality and capacity of biocontrol of phytopathogenic fungi - Mendez-Trujillo, Vianey; Gonzalez Mendoza, Daniel; Grimaldo-Juarez, Onecimo; Ceceña-Duran, Carlos; Tzintzun-Camacho, Olivia; Duran-Hernández, Dagoberto (Revista Colombiana de Investigaciones Agroindustriales, 2022)
In the present study, the biological quality and cell viability of different microbial inoculants marketed in Baja California, Mexico, was carried out. For this purpose, the antagonistic capacity was determined in triplicate by means of dual confrontation with phytopathogenic fungi, determination of cell viability using the serial dilution technique in culture medium; as well as the review of compliance with the packaging criteria based on the Mexican regulations in the products: Bioben, T-22, Funqui, Agroderma, Bio-Tilis, Enerbac, Fus-Out and Bacillus 1537. The results showed that the products Agroderma, Bacillus 1537 and Fus-Out, no health registration submitted. On the other hand, the viability of the inoculants evaluated by means of the plate count technique, showed values ​​of CFU/g or CFU/mL, lower than those indicated by the labels of the commercial inoculants. The results of antagonism of biological fungi against phytopathogenic fungi: Alternaria alternata, Macrophomina sp., Fusarium solani, and Botrytis sp., showed that only the product formulated based on Bacillus 1537 presented an inhibitory effect greater than 50% on phytopathogens. evaluated. In contrast, the products formulated based on mycoparasitic fungi, showed a lower efficiency of inhibition of phytopathogenic fungi, being the Funqui inoculant, the one that presented the capacity to inhibit their growth by 50%. Finally, Baja California has a wide presence of commercial inoculants; however, its quality and biological efficiency is variable against the pathogens present in the agricultural soils of the region.